Lymphatic Vessel Invasion in Routine Pathology Reports of Papillary Thyroid Cancer - Chiapponi, Costanza; Alakus, Hakan; Schmidt, Matthias; Faust, Michael; Bruns, Christiane J.; Büttner, Reinhard; Eich, Marie-Lisa; Schultheis, Anne M. (Frontiers in Medicine, 2022)
Abstract Purpose It is not mandatory to report lymphatic vessel invasion in pathology reports of papillary thyroid cancer (PTC) according to current UICC TNM classification. However, there is some evidence for its correlation with lymph nodal metastasis (LNM) and prognosis. The aim of the present study was to explore the clinical implication of lymphatic vessel invasion documentation of PTC, because pathology reports play a pivotal role for postsurgical clinical decision-making in endocrine tumor boards. Methods Patients undergoing postoperative radioiodine treatment for PTC at the University Hospital of Cologne, Germany between 12/2015 and 03/2020 were identified. Pathology reports were screened for documentation of lymphatic vessel invasion. Patients’ demographics and clinico-pathologic data documented, including lymphatic vessel invasion and lymph nodal involvement were analyzed. Results A total of 578 patients were identified and included. Lymphatic vessel invasion was reported in pathology reports of 366 (63.3%) and omitted in 112 (36.7%) patients. Positive lymphatic vessel invasion (L1) was diagnosed in 67 (18.3%) of 366 patients and was documented as absent (L0) in 299 (81.7%) patients. Lymph nodal (N) status was positive (N+) in 126 (45.6%) and negative (N0) in 150 (54.3%) of these patients. In 54 (80.6%) L1 cases N+ status and in 137 (65.6%) L0 cases N0 status was diagnosed. In 13 (19.4%) cases with L1 status, there were no LNMs (L1 N0). 72 (34.4%) patients had LNM despite L0 status (L0 N+). The sensitivity and specificity of LVI reporting for LNM were 0.42 and 0.91, respectively. Conclusion In routine pathology reports of PTC used for indication to postoperative radioiodine treatment by a German endocrine tumor board, lymphatic vessel invasion was found to be reported inconsistently and mostly as L0. L1 diagnoses however, reliably correlated with reported LNM and might thus be relevant for clinical decision-making. For this reason we advocate for standardized pathologic reassessment of lymphatic vessel invasion; in particular for cases where lymph nodes are not included in the pathologic specimen, and if L0 is documented.